2011
DOI: 10.1007/s11238-011-9255-6
|View full text |Cite
|
Sign up to set email alerts
|

Parametric multi-attribute utility functions for optimal profit under risk constraints

Abstract: International audienceWe provide an economic interpretation of the practice consisting in incorporating risk measures as constraints in an expected prospect maximization problem. For what we call the infimum of expectations class of risk measures, we show that if the decision maker (DM) maximizes the expectation of a random prospect under constraint that the risk measure is bounded above, he then behaves as a generalized expected utility maximizer in the following sense. The DM exhibits ambiguity with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Usually, the value of the risk aversion depends on the decision maker's behavior. In Seck et al, (Seck et al (2012)), it is shown that under the assumption of some particular formulation of a class of risk measures, maximizing a profit subject to these risk constraints is equivalent to maximizing a certain class of multi-attribute utility functions. These multi-attribute utility functions express loss aversion instead of risk aversion.…”
Section: Illustrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the value of the risk aversion depends on the decision maker's behavior. In Seck et al, (Seck et al (2012)), it is shown that under the assumption of some particular formulation of a class of risk measures, maximizing a profit subject to these risk constraints is equivalent to maximizing a certain class of multi-attribute utility functions. These multi-attribute utility functions express loss aversion instead of risk aversion.…”
Section: Illustrationmentioning
confidence: 99%
“…Two classes of entropic risk measures have been compared in Brandtner et al (2018), namely coherent or convex. These properties of risk measures are discussed largely in the literature and express some nice properties in terms of decision making strategies or solving complex portfolio optimization problems, see Cheridito et al (2005), Detlefsen and Scandolo (2005), Ben-Tal and Teboulle (2007), Ruszczynski and Shapiro (2004), Föllmer and Penner (2006), Seck et al (2012). Entropic risk measures have an exponential function representation.…”
Section: Introductionmentioning
confidence: 99%
“…It is useful for investors in practice to know relationships between the maximal utility approach and risk measures like for example value-at-risk (V aR) or conditional value-at-risk (CV aR). Seck et al in [35,3] examine connection between risk measures and parameterized families of loss aversion utility functions. For each risk measure they provide a class of associated utility functions, for which the problem of maximizing profit subject to a risk measure constraint and the max-min problem of optimization over the class of utility functions are equivalent.…”
Section: Introductionmentioning
confidence: 99%